Biotechnological potential of cassava residues: Peel, bagasse and wastewater - Costa, Siddhartha G.V.A.O. [UNESP]; Nitschke, Marcia; Contiero, Jonas [UNESP] (My University, 2011)
Advances in industrial biotechnology offer potential opportunities for the economic utilization of agro-industrial residues, such as those from the cassava processing industry. Three main types of residue are generated during the industrial processing of cassava: peels and bagasse (solid); and wastewater (liquid). Both types of waste are poor in protein content, but are carbohydrate-rich residues and generated in large amounts during the production of flour (which generates more solid residues) and starch (which generates more liquid residues) from the tubers. Waste treatment and disposal costs constitute a huge financial burden to the cassava processing industry as well as an environmental problem. Therefore, there is a great need for the better management of these waste products. Due to its rich organic nature, cassava residue can serve as an ideal substrate for microbial processes in the production of different products. Attempts have been made to produce products such as organic acids, flavor and aroma compounds, mushrooms, methane and hydrogen gas, enzymes, ethanol, lactic acid, biosurfactants, polyhydroxy alkanoate, essential oils, xanthan gum and fertilizer from cassava bagasse, peels and wastewater. The use of cassava residues as feedstock in bio technological processes is a viable alternative that can contribute toward a reduction in production costs, an increase in the economic value of these residues and the minimization of environmental problems related to waste discharge. This study reviews processes and products developed for aggregating value to cassava residues through biotechnological means, demonstrating the potential of this agro-industrial raw material. © 2012 by Nova Science Publishers, Inc. All rights reserved.